Cardiovascular risk factors in adolescents with prediabetes. Issue 9 (22nd May 2018) - Casagrande, S. S.; Menke, A.; Linder, B.; Osganian, S. K.; Cowie, C. C.
Abstract: Aims: Adolescents with Type 2 diabetes are more likely to have cardiovascular disease (CVD) risk factors but there are few data available among adolescents with prediabetes. We characterized CVD risk factors among adolescents with prediabetes in the USA and compared levels of those risk factors with adolescents with normal glucose. Methods: The 2005–2014 National Health and Nutrition Examination Survey, a nationally representative cross‐sectional survey, included 2843 adolescents aged 12–19 years after excluding those with diabetes. Prediabetes was based on an HbA1c, a fasting plasma glucose or a 2‐h plasma glucose. We determined cardiometabolic risk factors in adolescents using age‐appropriate cut‐off points. We calculated odds ratios (OR) and 95% confidence intervals (CI) of these outcomes associated with having prediabetes compared with normal glucose levels. Results: The weighted prevalence of prediabetes was 17.4%. After adjustment, prediabetes (vs. normal glucose) was associated with obesity (OR 1.86, 95% CI 1.35–2.55), low HDL‐cholesterol (OR 1.62, 95% CI 1.08–2.44), high triglycerides (OR 1.61, 95% CI 1.12–2.30) and elevated liver transaminase (OR 2.09, 95% CI 1.19–3.67), but not with hypertension (OR 1.77, 95% CI 0.88–3.54), elevated total cholesterol (OR 1.30, 95% CI 0.82–2.06), elevated LDL‐cholesterol (OR 1.59, 95% CI 0.88–2.88) or albuminuria (OR 1.24, 95% CI 0.76–2.02). Conclusions: US adolescents with prediabetes are more likely to have obesity, low HDL‐cholesterol, high triglycerides and elevated liver transaminase than adolescents with normal glucose. Addressing prediabetes in youth is important for the prevention of Type 2 diabetes and long‐term comorbidity. What's new?: Adolescents with Type 2 diabetes are more likely to have cardiovascular disease (CVD) risk factors but there are few data available among adolescents with prediabetes. Using a nationally representative survey, we found that US adolescents with prediabetes were more likely to have obesity, low HDL‐cholesterol, high triglycerides and elevated liver transaminase than adolescents with normal glucose. We observed increasing odds of these health outcomes beginning at levels below the cut‐off point for prediabetes. Addressing prediabetes and comorbidity in youth is important to reduce the risk of Type 2 diabetes and the risk of substantial long‐term health consequences.